Santa & company - Michaels, Fern (Kensington Publishing Corp., 2023)
"When longtime friends Amy, Frankie, Rachael and Nina reunited for a holiday singles cruise, it not only deepened their bond, it changed their lives. Now they're getting together for another adventure, and what better winter setting than a fabulous ski lodge? Crisp snow and fresh air by day, cozy fires and delicious food by night, capped off by meeting up with their significant others for a New Year's Eve celebration it's perfect. At least, it's perfect until Frankie decides to go snowshoeing alone. When she twists her ankle right after losing her phone in the snow, Frankie wonders how she'll be able to summon help only to be rescued by a reclusive Grizzly Adams lookalike who lives nearby and introduces himself as Troy Manchester. Troy saves the day by helping the injured Frankie back to the ski lodge, but in the process, encounters a part of the L.A. life he's tried to leave behind. Nina, visiting the gift shop to buy magazines for a recuperating Frankie, is similarly shocked to glimpse someone to whom she was once connected. Even in this unlikely spot, it seems there s no way to avoid their pasts. And as the mischievous Rachael and her sidekick Amy go to great lengths to patch up old friendships and spread the spirit of the season, the New Year may contain all kinds of new beginnings"--